Seasonal Cycle and Annual Reversal of the Somali Current in an Eddy‐Resolving Global Ocean Model. Issue 9 (17th September 2018) - Wang, He; McClean, Julie L.; Talley, Lynne D.; Yeager, Stephen
Abstract: The annual cycle of the Somali Current is studied using a forced strongly eddy‐active global ocean general circulation model. The annual cycle and timing of the reversal of the Somali Current differ depending on the location along the coast of northeastern Africa. A momentum budget analysis calculated from the model output shows that both annual Rossby waves and the life cycle of the Great Whirl impact the northern part of the Somali Current (roughly 5°N to 10°N). In particular, the nonlinear term is of leading order importance when the Great Whirl is present. This is in contrast to the leading‐order geostrophic balance between 2°N and 5°N. South of 2°N, equatorial dynamics prevail, and the nonlinear term is again important, and its reversal is strongly affected by the northward flowing East African Coastal Current. Alongshore wind forcing is influential at all latitudes, but only the transition in flow direction during boreal spring between 2°N and 5°N directly follows that of the wind. Plain Language Summary: The Somali Current flows along the western boundary of northwest Africa in the Arabian Sea. Unlike other strong western boundary currents, the Somali Current reverses seasonally; its reversal has been attributed to the seasonally reversing Indian monsoon wind. The Somali Current is important for both regional climate and ecology and can potentially impact monsoon precipitation. Due to the difficulties in collecting observations due to piracy in the western Arabian Sea over the past decade, the scientific community has relied on numerical ocean models to enhance understanding of the behavior of this current. In this study, we use a global state‐of‐the‐art numerical ocean model that resolves "weather‐scale" features in the ocean, that is, mesoscale eddies, to understand Somali Current drivers and what controls its seasonal reversal. We find that in addition to the local wind, the Somali Current system is influenced by winds and oceanic phenomena distant from the region, which leads to different reversal times in different parts of the current. As a result, we identify three distinct regimes along the Somali Current and analyze their respective dynamics. Key Points: Three dynamical regimes are identified in the Somali Current based on their different annual cycles and leading‐order momentum balances Nonlinearity and remote forcing are important north of 5°N (Great Whirl and Rossby wave) and close to the equator (cross‐equatorial current) Local wind is important in all three regimes, but only the reversal of surface flow between 2° and 5°N directly follows that of the wind